Quantifying the inovation of cosmetic formulations that contains phenolic rich fruit extracts as fotoprotective bioactives - Mota, Milleno Dantas; Chinalia, Fábio Alexandre; Silva, Lidércia Cavalcanti Ribeiro Cerqueira e (Revista de Ciências Médicas e Biológicas, 2021)
Introduction: sunscreen is a cosmetic used to protect human skin from the deleterious effects of UV radiation and thus minimize the risks of developing skin cancer. Extracts produced from fruits, such as Abiu, Guava, Rambutan and Grape, have significant concentrations of chromophores and phenolic substances that have the ability to absorb UV light and neutralize free radicals. The production of cosmetics from naturally occurring substances with such activities will be of great importance for Brazilian industry and could reduce the cost of production, given the large existing biodiversity in the country. Objectives: carry out a patent search for formulations and cosmetic products that contains phenolic rich fruit extracts as photoprotective and antioxidant bioactives. Methodology: a survey of patents was carried out in the database of the National Institute of Intellectual Property (INPI) and the European Patent Office (EPO), covering a time period between 2008 and 2018, using a combination of keywords related to herbal cosmetics and sunscreens. Results: this research identifies a significant number of patents related to plant extract in association with sunscreen product, however, no patent filings were identified for cosmetic products containing extracts of the evaluated fruits, either alone or in combination, for photoprotective and antioxidant purposes. Conclusion: the Brazilian and international market for sun care products moves millions to billions of dollars annually and have a significant annual growth prospect. Considering the great biodiversity existing in the country, the production of cosmetics from naturally occurring substances with such activities will be of great importance for the Brazilian industrial sector.